The Challenges in Establishing a Participatory Qanun of Gampong - Sulaiman Sulaiman; T. Muttaqin Mansur; M. Adli Abdullah; Nellyana Roesa; Lia Sautunnida (Universitas Syiah Kuala, 2021)
This article aims to analyze the challenges of establishing a participatory qanun of gampong. This research was conducted in the village under Syiah Kuala University supervision, Ingin Jaya sub-district, Aceh Besar. This study examined into legal resources, particularly qanuns, in order to analyze the participatory law-making process. The substitution of Aceh Besar Qanun Number 11 Year 2009 with Aceh Besar Qanun Number 2 Year 2020 has caused several legal issues, especially with regard to the supervision of gampong qanuns, which are no longer have a legal basis. Starting with the concept of legal development, replenishment is essential. Due to the lack of rules that act as guidelines, the process of establishing qanuns of gampong has become more complicated. The main reason is that participatory processes are hard to accomplish. It is advised to the Aceh Besar District Government to draft recommendations for the drafting qanun of gampong as soon as possible as a form of guidance for the gampong government. This guidance will also substantially help the gampong government's efforts in preparing numerous requirements for qanuns of gampong.